Delivery of Human Stromal Vascular Fraction Cells on Nanofibrillar Scaffolds for Treatment of Peripheral Arterial Disease - Hu, Caroline; Zaitseva, Tatiana S.; Alcazar, Cynthia; Tabada, Peter; Sawamura, Steve; Yang, Guang; Borrelli, Mimi R.; Wan, Derrick C.; Nguyen, Dung H.; Paukshto, Michael V.; Huang, Ngan F. (Frontiers in Bioengineering and Biotechnology, 2020)
Cell therapy for treatment of peripheral arterial disease (PAD) is a promising approach but is limited by poor cell survival when cells are delivered using saline. The objective of this study was to examine the feasibility of aligned nanofibrillar scaffolds as a vehicle for the delivery of human stromal vascular fraction (SVF), and then to assess the efficacy of the cell-seeded scaffolds in a murine model of PAD. Flow cytometric analysis was performed to characterize the phenotype of SVF cells from freshly isolated lipoaspirate, as well as after attachment onto aligned nanofibrillar scaffolds. Flow cytometry results demonstrated that the SVF consisted of 33.1 ± 9.6% CD45+ cells, and to a lesser extent of CD31+ cells. Among the CD31-/CD45- subpopulation, 45.4 ± 20.0% of the cells co-expressed CD34. Although the subpopulations of SVF did not change significantly after attachment to the aligned nanofibrillar scaffolds, protein secretion of vascular endothelial growth factor (VEGF) significantly increased by 6-fold, compared to SVF cultured in suspension. Importantly, when SVF-seeded scaffolds were transplanted into immunodeficient mice with induced hindlimb ischemia, the cell-seeded scaffolds induced a significant higher mean perfusion ratio after 14 days, compared to cells delivered using saline. Together, these results show that aligned nanofibrillar scaffolds promoted cellular attachment, enhanced the secretion of VEGF from attached SVF cells, and their implantation with attached SVF cells stimulated blood perfusion recovery. These findings have important therapeutic implications for the treatment of PAD using SVF.